Mechanism of innovation and standardization driving company competitiveness in the digital economy - Yang, Jing; Zhou, Lijun; Qu, Yuyang; Jin, Xiang; Fang, Shishi (Journal of Business Economics and Management, 2023)
Data have changed the characteristics of the global value chain in the context of digital economy. Standards and innovation are the key facilitators of digital economy. Considering the collaborative development of innovation and standardization, this paper constructs a theoretical model of the impact of innovation and standardization levels on company competitiveness. Furthermore, the moderating effect of the coupling coordination of innovation and standardization was analyzed for both factors. In total, 171 listed companies in the field of digital economy were selected as the research. The results indicated that a company’s level of innovation and standardization influences company competitiveness. Moreover, the relationship between innovation and standardization was found to be a coordinating development relationship and not a conventional promotion or hindrance. This article also proposed some pertinent suggestions for companies involved in the global value chain competition.